Maimonides's Rationalization of the Incest Taboo, Its Reception in Thirteenth-Century Kabbalah, and Their Affinity to Aquinas - Sachs-Shmueli, Leore (Harvard theological review, 2021)
This article discusses Maimonides's rationale for the incest taboo and traces its reception in Christian and kabbalistic traditions in the thirteenth century. Tracing the reception of Maimonides's view enables recognition of the resemblance between Maimonides and Aquinas, the ambivalent stance toward Maimonides's explanation expressed by Nahmanides, and the incorporation of Maimonides's reasoning in one of the most systematic and enigmatic works of kabbalistic rationalization of the commandments, the Castilian Kabbalist Joseph of Hamadan's The Book of the Rationales of the Negative Commandments. R. Joseph's acceptance of Maimonidean principles and his integration of them in the theurgic Kabbalah reveal a conflict in the heart of its system and teach us about an important aspect of the theory of sexuality in Kabbalah. The inquiry offered here examines the inter-relations between divergent medieval religious trends in constructing the role of sexuality. Instead of the common presentation of Kabbalah as diverging from the ascetic positions of Jewish philosophy and Christianity, this analysis will elucidate Kabbalah's continuity with them.